Luis David Aguilar - Hombres de viento (1978) - Aguilar Valdizán, David Alonso (2024)
Cinema, having inherited from Wagnerian opera its surreptitious desire to become the total work of art, uses music to convey everything that the image cannot by itself, but when cinema becomes poetry then we have a different kind of interaction. This is the case of the film Hombres de viento by director José Antonio Portugal, in which images, narration and music are combined to immerse the viewer in the story of the workers in the canteras de sillar.